“Whoopee! We’re All Gonna Die!”: The Inimitability of Woodstock - Bajić, Marina (Music with a Message: Words, Music and Propaganda 2, 2025)
Woodstock Music and Art Festival is one of history’s best known and most culturally significant event. At the height of the war between the United States of America and Vietnam, it allowed the people to come together and enjoy three days of love, peace, and music. However, with later iterations of festivals bearing the name Woodstock, the core message of love and peace lost itself among the music and the people. If Woodstock 1969 brough together people who wanted to make art, enjoy music and enjoy each other’s company, while simultaneously express their dissatisfaction with the Establishment, the 1994 and 1999 versions brough forth people who only wanted to express their dissatisfaction with each other. A festival with the name Woodstock was never put on again.